Ciencias sociales 9 - QUINTEROS, Silvina; COLOMBO, Edgardo; ROUGIER, Marcelo; CORTES, Ricardo (KAPELUSZ, 2000)
AUTORES : ELBAUM, Jorge; MICELI, Paola; DELL'ELICINE, Eleonora; ARCA, Claudio; GARRIGA, María Cristina; MORANDO, Nelva